Amplitude analysis of B0 → D[bar]0K+π-decays - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
The Dalitz plot distribution of B0→¯D0K+π− decays is studied using a data sample corresponding to 3.0 fb−1 of pp collision data recorded by the LHCb experiment during 2011 and 2012. The data are described by an amplitude model that contains contributions from intermediate K∗(892)0, K∗(1410)0, K∗2(1430)0 and D∗2(2460)− resonances. The model also contains components to describe broad structures, including the K∗0(1430)0 and D∗0(2400)− resonances, in the Kπ S-wave and the Dπ S- and P-waves. The masses and widths of the D∗0(2400)− and D∗2(2460)− resonances are measured, as are the complex amplitudes and fit fractions for all components included in the amplitude model. The model obtained will be an integral part of a future determination of the angle γ of the Cabibbo-Kobayashi-Maskawa quark mixing matrix using B0→DK+π− decays.